(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
This article addresses the participation of machines in the show A Última Invenção by the artistic collective De Pernas Pro Ar from the city of Canoas/RS. In analyzing the procedures used in the construction of the machines and the nature of the scenic actions established between the performer and the robotic machines, the importance of the memory of common objects and the playful interaction is identified as key to imparting a sensitive layer to these machinelike devices, whose appearance is far from human. It is argued that such devices constitute machine-actors that integrate into the scene, not to replace the actor, but to diversify the models of automatons in theater.